Studi Komparatif Keterikatan Tempat (Place Attachment) pada Komunitas Relokasi dan In-Situ Pascabencana Likuifaksi di Sulawesi Tengah - Najib, Adnagmesha Magfirah Ramadhani; Setiawan, Bakti (Jurnal Peweka Tadulako, 2025)
Post-disaster housing reconstruction is a crucial stage that often focuses on physical recovery, while the restoration of the emotional connection between people and their homes is frequently overlooked. This raises an urgent need to understand how reconstruction policies affect the human dimension of survivors. Therefore, this study aims to comparatively analyze the impact of two reconstruction schemes, relocation to permanent housing (Huntap) and in-situ stimulant funds, on the recovery of place attachment among the survivor community of Dusun III Vou, Central Sulawesi. This research is using a qualitative method with a comparative case study design, data were collected through in-depth interviews and field observations. The findings indicate that the two approaches yield fundamentally different consequences. The relocation scheme succeeded in providing physical security from environmental trauma but significantly severed the community's functional ties to their agrarian livelihoods. Conversely, the in-situ scheme successfully maintained socio-economic continuity and social cohesion, although survivors must live with place-based trauma. This study concludes that the choice of reconstruction policy represents a dilemma between recovering physical security and ensuring socio-economic sustainability, implying the need for more holistic recovery models in the future.